2021
DOI: 10.1515/tnsci-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided ethyl alcohol injection to the deep branch of the ulnar nerve to relieve hand spasticity in stroke patients: A case series

Abstract: Hand spasticity with a flexor pattern is a common problem affecting stroke patients and can result in pain, contractures, esthetic concerns, skin maceration, and overall loss of function. Poststroke (≥6 months) hemiparetic adult patients having a Modified Ashworth Scale (MAS) score of ≥1 for metacarpophalangeal flexion and thumb adduction spasticity were selected to receive an ultrasound-guided 20% ethyl alcohol block performed perineurally at the level of the deep branch of the ulnar nerve. Their MAS scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…19 Previous studies examining ethanol or phenol-only injections found pain and dysesthesia among 5%-22% of patients. 7,14,15,20,21 No patients in our cohort experienced potentially life-threatening complications such as severe respiratory infection as a result of motor weakness. The use of ultrasound, in addition to electrical stimulation, may have helped limit the adverse events in our study.…”
Section: Safety Profile Of Injectionsmentioning
confidence: 91%
See 2 more Smart Citations
“…19 Previous studies examining ethanol or phenol-only injections found pain and dysesthesia among 5%-22% of patients. 7,14,15,20,21 No patients in our cohort experienced potentially life-threatening complications such as severe respiratory infection as a result of motor weakness. The use of ultrasound, in addition to electrical stimulation, may have helped limit the adverse events in our study.…”
Section: Safety Profile Of Injectionsmentioning
confidence: 91%
“…Other potential adverse effects noted in the literature include nausea and vomiting, 5,12 distal swelling, 13,14 and irritation/ bruising/swelling at the injection site. However, the use of ultrasound guidance in addition to electrical stimulation may increase accuracy and effectiveness of needle placement, avoiding inadvertent injury to sensory branches, [15][16][17] and thus decreasing the adverse effects of ethanol neurolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation